TINGKAT BERPIKIR KREATIF PESERTA DIDIK DALAM MENYELESAIKAN MASALAH MATEMATIKA OPEN ENDED BERDASARKAN GAYA KOGNITIF REFLEKTIF DAN IMPULSIF - Rahmatina, Siti; Ismi, Khairul (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
This study aims to determine the level of creative thinking of students in solving math problems. This type of research is a verification qualitative research. The research subjects were eight people, the first grade students of Ar-Raniry Banda Aceh UIN. Subject selection was made based on the Matching Familiar Figure Test (MFFT), namely four reflective students and four impulsive students. The research data were obtained from the research subjects' written answers, namely the mathematics creative thinking test (TBKM) and the results of the interview. To test the credibility of the data the researcher triangulated. In this study, the triangulation used was the method triangulation by comparing TBKM and interviews. Students' creative thinking skills can be seen based on the achievement of mathematical creative thinking indicators. The results of the study are as follows, the reflective subject's creative thinking level 1 on compound interest calculation material is level 4, which meets four indicators of fluency, novelty, flexibility, and elaboration, the creative thinking level of reflective subject 1 on the straight-line equation related to supply and demand functions is the level 3 namely meeting the three indicators of fluency, flexibility, and elaboration. The reflective subject's creative thinking level 2 on compound interest calculation material is level 3, which is fulfilling three indicators of fluency, flexibility, and elaboration, the reflective subject's creative thinking level 2 on the straight-line equation related to supply and demand functions is level 4, which meets four indicators of fluency, novelty , flexibility and elaboration. The level of reflective subject creative thinking 3 on compound interest calculation material is level 3, which is fulfilling three indicators of fluency, novelty, and elaboration, the level of creative thinking reflective subject 3 on the material of straight-line equations related to supply and demand functions is level 1 namely meeting two indicators of fluency and elaboration. The reflexive subject's creative thinking level 4 on compounded calculation material is level 4, which is fulfilling four indicators of fluency, novelty, flexibility, and elaboration, the reflective subject's creative thinking level 4 on the straight-line equation material related to supply and demand functions is level 4, which is meeting four indicators fluency, novelty, flexibility and elaboration. The level of creative thinking of the subjects Impulsive 1, Impulsive 2, and Impulsive 4 on the compound interest calculation material and on the straight line equation material is level 1 which satisfies two indicators of fluency and elaboration. The level of creative thinking of the impulsive subject 3 on the compound interest calculation material and on the straight line equation material is level 3 which is to fulfill three indicators of fluency, flexibility, and elaboration.